Electrochemical device and electronic device

JP2025041748AActive Publication Date: 2025-03-26NINGDE AMPEREX TECHNOLOGY LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024223908
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-26
Estimated Expiration
2040-10-15

Smart Images

  • Figure 2025041748000001
    Figure 2025041748000001
  • Figure 2025041748000002
    Figure 2025041748000002
  • Figure 2025041748000003
    Figure 2025041748000003
Patent Text Reader

Abstract

To provide an electrochemical device that has improved high-temperature storage properties and overcharge resistance properties.SOLUTION: An electrochemical device includes a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode includes a negative electrode charge collector, and a negative electrode mixture layer formed on the negative electrode charge collector. the negative electrode mixture layer includes a negative electrode active material and also has specific adhesive strength for the negative electrode active material, and the electrode includes ester propionate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of energy storage, in particular to electrochemical and electronic devices, and more particularly to lithium-ion batteries. [Background technology]

[0002] In recent years, with the continuous expansion of the industrial scale of batteries and the continuous development of related technologies, the applications of electrochemical devices (such as lithium-ion batteries) have expanded significantly, and they have become the main energy storage devices in electronic products. With the increasing demand, the performance requirements for lithium-ion batteries are also increasing, and the production process is also continuously improving.

[0003] There are many types of raw materials, each with its own advantages and disadvantages, so when using them, it is common to combine multiple types of raw materials. However, when different materials are mixed together, there is a possibility that they may not be compatible, which may cause a decrease in battery performance.

[0004] In view of the above, there is a need to provide electrochemical and electronic devices with improved properties. Summary of the Invention

[0005] SUMMARY OF THE DISCLOSURE Embodiments of the present invention provide electrochemical and electronic devices with improved high temperature storage and overcharge resistance characteristics, which at least in part solves at least one of the problems in the related art.

[0006] In one aspect of the present invention, there is provided an electrochemical device including a positive electrode, a negative electrode, and an electrolyte, the negative electrode including a negative electrode current collector and a negative electrode mixture layer formed on the negative electrode current collector, the negative electrode mixture layer including a negative electrode active material, and an adhesive strength between the negative electrode active materials is FN / cm 2 where F is in the range of 100 to 500, and the electrolyte contains a propionate ester.

[0007] According to an embodiment of the present invention, the negative electrode mixture layer includes rubber, and the rubber includes at least one of styrene-butadiene rubber, isoprene rubber, butadiene rubber, fluororubber, acrylonitrile-butadiene rubber, and styrene-propylene rubber.

[0008] According to an embodiment of the present invention, the rubber further comprises at least one of an acrylic functional group, a chlorotrifluoroethylene functional group, and a hexafluoropropylene functional group.

[0009] According to an embodiment of the present invention, when the content of the propionate ester is X% with respect to the weight of the electrolyte, X is in the range of 5-65.

[0010] According to an embodiment of the present invention, F and X satisfy 1.6≦F / X≦100.

[0011] According to an embodiment of the present invention, the specific surface area of ​​the negative electrode mixture layer is set to Am 2 / g, A is in the range of 2 to 5.

[0012] According to an embodiment of the present invention, F and A satisfy 20≦F / A≦250.

[0013] According to an embodiment of the present invention, the negative electrode active material is (a) having a median diameter of 5 μm to 30 μm; (b) comprising at least one of artificial graphite, natural graphite, mesocarbon microbeads, soft carbon, hard carbon, amorphous carbon, a silicon-containing material, a tin-containing material, and an alloy material; (c) containing a metal, the metal containing at least one of molybdenum, iron, or copper, and the content of the metal relative to the weight of the negative electrode mixture layer is 0.05% or less; Satisfy at least one of the following:

[0014] According to an embodiment of the present invention, the electrolyte solution is i) fluorocarbonates, ii) a compound having a cyano group, iii) lithium difluorophosphate, iv) a compound of formula 1, The present invention further includes at least one of the following: [ka] R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are each independently hydrogen or C1-C 10 is an alkyl group, L1 and L2 each independently represent -(CR 7 R 8 ) n - and R 7 and R 8 are each independently hydrogen or C1-C 10 is an alkyl group, and n is 1, 2 or 3.

[0015] According to an embodiment of the present invention, the compound of formula 1 is [ka] Includes at least one of the following:

[0016] According to an embodiment of the present invention, the content of the compound of formula 1 is in the range of 0.01% to 5% by weight of the electrolyte.

[0017] According to the embodiment of the present invention, when the content of the compound having a cyano group is b% with respect to the weight of the electrolyte solution, b is in the range of 0.01 to 10.

[0018] According to an embodiment of the present invention, X and b satisfy 0.5≦X / b≦200.

[0019] In another aspect, the present invention provides an electronic device comprising an electrochemical device according to the present invention.

[0020] Further aspects and advantages of the present invention are set forth in part in the following description, and are illustrated or elucidated through examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The following examples of the present invention are described in detail, but should not be construed as limiting the present invention.

[0022] Unless otherwise stated, the following terms used herein have the meanings indicated below.

[0023] In specific embodiments and claims, a list of terms connected with the term "at least one of" means any combination of the listed terms. For example, if term A and term B are listed, "at least one of A and B" means A only, B only, or A and B. In another example, if term A, term B, and term C are listed, "at least one of A, B, and C" means A only, B only, C only, A and B (excluding C), A and C (excluding B), B and C (excluding A), or all of A, B, and C. Term A may include one element or multiple elements. Term B may include one element or multiple elements. Term C may include one element or multiple elements. The term "at least one of" has the same meaning as the term "at least one of".

[0024] The term "alkyl group" as used herein contemplates a straight chain saturated hydrocarbon structure having 1 to 20 carbon atoms. "Alkyl group" further contemplates a branched chain or cyclic hydrocarbon structure having 3 to 20 carbon atoms. When an alkyl group having a specific number of carbon atoms is specified, it is intended to include all geometric isomers having that number of carbon atoms. Thus, for example, "butyl" is meant to include n-butyl, sec-butyl, isobutyl, tert-butyl, and cyclobutyl, and "propyl" includes n-propyl, isopropyl, and cyclopropyl. Illustrative examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, ethylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, n-heptyl, octyl, cyclopropyl, cyclobutyl, norbornyl, and the like.

[0025] The term "halogenated" as used herein refers to a group in which the hydrogen atoms are partially or fully replaced with halogen atoms (eg, fluorine, chlorine, bromine or iodine).

[0026] With the widespread application of electrochemical devices (such as lithium ion batteries), the requirements for the properties of electrochemical devices, especially their safety, are increasing. When a lithium ion battery is under high temperature or overcharged conditions, it is easy to generate a large amount of heat inside the battery. If the heat cannot be uniformly released, it will cause problems such as aging, expansion, deformation, and even explosion of the lithium ion battery.

[0027] In order to solve the above problems, the present invention uses a combination of a negative electrode active material having a specific adhesive strength and an electrolyte containing a propionic acid ester, thereby preventing the negative electrode from breaking during high-temperature storage and allowing the capacity of the electrochemical device to be fully utilized, thereby significantly improving the high-temperature storage characteristics and overcharge prevention characteristics of the electrochemical device.

[0028] In one embodiment, the present invention provides an electrochemical device comprising a positive electrode, a negative electrode, and an electrolyte as described below.

[0029] I, negative electrode The negative electrode includes a negative electrode current collector and a negative electrode mixture layer disposed on one or two surfaces of the negative electrode current collector.

[0030] 1. Negative electrode mixture layer The negative electrode mixture layer includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material. The negative electrode mixture layer may be one layer or multiple layers, and each layer of the multiple layers of negative electrode active materials may include the same or different negative electrode active materials. The negative electrode active material is any material that can reversibly absorb and release metal ions, such as lithium ions. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material, thereby preventing lithium metal from unintentionally depositing on the negative electrode during charging.

[0031] The electrochemical device of the present invention has an adhesive strength between the negative electrode active materials of FN / cm 2 is in the range of 100 to 500. In some embodiments, F is in the range of 150 to 450. In some embodiments, F is in the range of 200 to 400. In some embodiments, F is 100, 150, 200, 250, 300, 350, 400, 450, 500, or in a range consisting of any two of the above values. When the adhesive strength between the negative electrode active materials is in the above range, the high temperature storage characteristics and overcharge resistance characteristics of the electrochemical device can be significantly improved.

[0032] The adhesive strength between negative electrode active materials is one of the parameters indicating the characteristics of the negative electrode active material, and can be adjusted by adding a specific substance (for example, rubber) or by controlling the composition of the negative electrode slurry, the application process, etc.

[0033] The adhesive strength between the negative electrode active materials can be measured by the following method. A negative electrode measuring 2 cm x 3 cm is cut out, the negative electrode mixture layer is peeled off from one side of the negative electrode, and the other side of the negative electrode is attached to a double-sided tape (product number: No. 515, manufactured by Nitto Denko Corporation) attached to a glass plate. Then, the negative electrode current collector is peeled off to obtain a negative electrode mixture layer attached to the double-sided tape as a measurement sample. The double-sided tape side of the measurement sample is attached to the tip (tip diameter is 0.2 cm) of the measurement head of a tacking tester (product name: TAC-II, manufactured by RHESCA Corporation). Next, a peel test is performed by pushing a measurement probe into the negative electrode mixture layer and pulling it away under the following conditions. In this peel test, the maximum load at which peeling occurs between the negative electrode active materials is measured. The obtained maximum load is measured by multiplying the cross-sectional area of ​​the measurement head (0.031 cm 2 ) and the value obtained is the adhesive strength between the negative electrode active materials.

[0034] The test conditions are as follows: The pressing speed of the measurement probe was 30 mm / min. The measurement probe was pressed for 10 seconds. The pressing force of the measuring probe is 3.9N. The measurement probe withdrawal speed is 600 mm / min.

[0035] In some embodiments, the negative electrode mixture layer includes a rubber, which can effectively improve the interface stability of the negative electrode mixture layer, thereby significantly improving the high-temperature storage characteristics and overcharge resistance characteristics of the electrochemical device.

[0036] In some embodiments, the rubber comprises at least one of styrene-butadiene rubber, isoprene rubber, butadiene rubber, fluororubber, acrylonitrile-butadiene rubber, and styrene-propylene rubber.

[0037] In some embodiments, the rubber further comprises at least one of acrylic, chlorotrifluoroethylene, and hexafluoropropylene functional groups.

[0038] In some embodiments, the rubber content is 10% or less based on the weight of the negative electrode mixture layer. In some embodiments, the rubber content is 8% or less based on the weight of the negative electrode mixture layer. In some embodiments, the rubber content is 5% or less based on the weight of the negative electrode mixture layer. In some embodiments, the rubber content is 3% or less based on the weight of the negative electrode mixture layer. In some embodiments, the rubber content is 2% or less based on the weight of the negative electrode mixture layer.

[0039] In some embodiments, the specific surface area of ​​the negative electrode mixture layer is 2 / g, A is in the range of 2 to 5. In some embodiments, A is in the range of 3 to 4. In some embodiments, A is 2, 2.5, 3, 3.5, 4, 4.5, or in the range consisting of any two of the above values. When the specific surface area of ​​the negative electrode mixture layer is in the above range, deposition of lithium on the negative electrode surface can be suppressed, and gas generation due to reaction between the negative electrode and the electrolyte can be suppressed, thereby further improving the high-temperature storage characteristics and overcharge resistance characteristics of the electrochemical device.

[0040] The specific surface area (BET) of the negative electrode mixture layer can be measured by the following method. Using a surface area meter (automatic surface area measurement device manufactured by Ohkura Riken), the sample is pre-dried for 15 minutes at 350°C under a nitrogen gas flow. Then, using a nitrogen-helium mixed gas in which the relative pressure of the nitrogen gas to the atmospheric pressure is precisely adjusted to 0.3, the measurement is performed by the nitrogen adsorption single-point BET method using the gas flow method.

[0041] In some embodiments, the adhesive strength between the negative electrode active materials FN / cm 2 and the specific surface area A m of the negative electrode mixture layer 2 / g satisfies 20≦F / A≦250. In some embodiments, 30≦F / A≦240. In some embodiments, 50≦F / A≦200. In some embodiments, 60≦F / A≦150. In some embodiments, F / A is 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 125, 150, 180, 200, 240, 250, or within a range consisting of any two of the preceding values. Adhesion strength FN / cm between negative electrode active materials 2 and the specific surface area A m of the negative electrode mixture layer 2 When / g satisfies the above relationship, the high-temperature storage characteristics and overcharge resistance characteristics of the electrochemical device can be further improved.

[0042] In some embodiments, the negative electrode active material has at least one of the following characteristics (a) to (c):

[0043] (a) Median diameter (D50) The median diameter (D50) of the negative electrode active material means the volume-based average particle diameter obtained by a laser diffraction / scattering method.

[0044] In some embodiments, the negative electrode active material has a median diameter of 5 μm to 30 μm. In some embodiments, the negative electrode active material has a median diameter of about 10 μm to about 25 μm. In some embodiments, the negative electrode active material has a median diameter of about 15 μm to about 20 μm. In some embodiments, the negative electrode active material has a median diameter of about 1 μm, about 3 μm, about 5 μm, about 7 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, or a median diameter within a range consisting of any two of the above values. When the median diameter of the negative electrode active material is within the above range, the irreversible capacity of the electrochemical device is small and it is easy to uniformly apply the negative electrode.

[0045] The median diameter of the negative electrode active material can be measured by the following method: The negative electrode active material is dispersed in a 0.2% aqueous solution (about 10 mL) of polyoxyethylene (20) sorbitan monolaurate, and the measurement is performed using a laser diffraction / scattering type particle size distribution analyzer (LA-700 manufactured by Horiba, Ltd.).

[0046] (b) Type of negative electrode active material In some embodiments, the negative electrode active material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, soft carbon, hard carbon, amorphous carbon, silicon-containing materials, tin-containing materials, and alloy materials.

[0047] In some embodiments, the shape of the negative active material includes, but is not limited to, fibers, spheres, grains, and flakes.

[0048] In some embodiments, the interlayer distance of the crystal lattice plane (002 plane) of the negative electrode active material is within a range of about 0.335 nm to about 0.360 nm, a range of about 0.335 nm to about 0.350 nm, or a range of about 0.335 nm to about 0.345 nm, based on an X-ray diffraction pattern by the Gakushin method.

[0049] In some embodiments, the negative electrode active material has a crystallite size (Lc) of greater than about 1.0 nm, or greater than about 1.5 nm, based on an X-ray diffraction pattern by the Gakushin method.

[0050] In some embodiments, the Raman R value of the negative electrode active material is greater than about 0.01, greater than about 0.03, or greater than about 0.1. In some embodiments, the Raman R value of the negative electrode active material is less than about 1.5, less than about 1.2, less than about 1.0, or less than about 0.5. In some embodiments, the Raman R value of the negative electrode active material is within the range consisting of any two of the above values.

[0051] The negative electrode active material has a thickness of 1580 cm -1 The Raman half-width at about 1580 cm of the negative electrode active material is not particularly limited. -1The Raman half-width in the vicinity is about 10 cm -1 Over or about 15cm -1 In some embodiments, the negative electrode active material has a peak at 1580 cm -1 The Raman half-width in the vicinity is about 100 cm -1 Less than 80cm -1 Less than 60cm -1 Less than or about 40cm -1 In some embodiments, the negative electrode active material has a peak at 1580 cm -1 The Raman half-width in the vicinity is within the range consisting of any two of the above values.

[0052] In some embodiments, the aspect ratio of the negative electrode active material is greater than about 1, greater than about 2, or greater than about 3. In some embodiments, the aspect ratio of the negative electrode active material is less than about 10, less than about 8, or less than about 5. In some embodiments, the aspect ratio of the negative electrode active material is within a range consisting of any two of the above values. When the aspect ratio of the negative electrode active material is within the above range, more uniform application can be achieved.

[0053] (c) Trace elements In some embodiments, the negative electrode active material includes a metal, the metal including at least one of molybdenum, iron, and copper, which can react with organic matter having poor electrical conductivity in the negative electrode active material, and thus is advantageous for the formation of a film on the surface of the negative electrode active material.

[0054] In some embodiments, the metal element is present in a small amount in the negative electrode mixture layer to avoid forming non-conductive by-products and adhering to the negative electrode surface. In some embodiments, the metal content is 0.05% or less based on the weight of the negative electrode mixture layer. In some embodiments, the metal content is 0.04% or less based on the weight of the negative electrode mixture layer. In some embodiments, the metal content is 0.03% or less based on the weight of the negative electrode mixture layer. In some embodiments, the metal content is 0.01% or less based on the weight of the negative electrode mixture layer. When the metal content in the negative electrode mixture layer is within the above range, the high temperature storage characteristics and overcharge resistance characteristics of the electrochemical device can be further improved.

[0055] In some embodiments, the negative electrode mixture layer further comprises at least one of a silicon-containing material, a tin-containing material, and an alloy material. In some embodiments, the negative electrode mixture layer further comprises at least one of a silicon-containing material and a tin-containing material. In some embodiments, the negative electrode mixture layer further comprises one or more of a silicon-containing material, a silicon carbon composite material, a silicon oxygen material, an alloy material, and a lithium-containing metal composite oxide material.

[0056] In some embodiments, the negative electrode mixture layer further includes one or more other types of negative electrode active materials, including, for example, metal elements and metalloid elements that can form an alloy with lithium. In some embodiments, examples of the metal elements and metalloid elements include, but are not limited to, Mg, B, Al, Ga, In, Si, Ge, Sn, Pb, Bi, Cd, Ag, Zn, Hf, Zr, Y, Pd, and Pt. In some embodiments, examples of the metal elements and metalloid elements include Si, Sn, and combinations thereof. Si and Sn have excellent lithium ion release capabilities and can provide high energy density to lithium ion batteries. In some embodiments, the other types of negative electrode active materials may further include one or more of metal oxides and polymer compounds. In some embodiments, the metal oxides include, but are not limited to, iron oxide, ruthenium oxide, and molybdenum oxide. In some embodiments, the polymer compounds include, but are not limited to, polyacetylene, polyaniline, and polypyrrole.

[0057] Negative electrode conductive material In some embodiments, the negative electrode mixture layer further includes a negative electrode conductive material, which may include any conductive material that does not undergo chemical change. Non-limiting examples of the conductive material include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.

[0058] Negative electrode binder In some embodiments, the negative electrode mixture layer further includes a negative electrode binder. The negative electrode binder can improve the bond between the negative electrode active material particles and the bond between the negative electrode active material and the current collector. The type of the negative electrode binder is not particularly limited, and may be any material that is stable against the electrolyte or the solvent used in manufacturing the electrode.

[0059] Examples of negative electrode binders include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, polyimide, cellulose, and nitrocellulose; rubber-like polymers such as styrene-butadiene rubber (SBR), isoprene rubber, butadiene rubber, fluororubber, acrylonitrile-butadiene rubber (NBR), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers and their hydrogenated products; ethylene-propylene-diene terpolymers (EPDM), and styrene-ethylene-butadiene-styrene copolymers. Thermoplastic elastomer-like polymers such as styrene-isoprene-styrene block copolymers and hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluoropolyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; polymer compositions having ionic conductivity of alkali metal ions (e.g., lithium ions), etc., but are not limited to these. The above negative electrode binders may be used alone or in combination as desired.

[0060] When the negative electrode mixture layer includes a fluorine-based polymer (e.g., polyvinylidene fluoride), in some embodiments, the content of the negative electrode binder is greater than about 1%, greater than about 2%, or greater than about 3% by weight of the negative electrode mixture layer. In some embodiments, the content of the negative electrode binder is less than about 10%, less than about 8%, or less than about 5% by weight of the negative electrode mixture layer. The content of the negative electrode binder is within the range consisting of any two of the above values.

[0061] solvent The type of solvent for forming the negative electrode slurry is not particularly limited, and may be any solvent capable of dissolving or dispersing the negative electrode active material, the negative electrode binder, and the thickener and conductive material used as necessary. In some embodiments, the solvent for forming the negative electrode slurry may be either an aqueous solvent or an organic solvent. Examples of aqueous solvents include, but are not limited to, water, alcohol, and the like. Examples of organic solvents include, but are not limited to, N-methylpyrrolidone (NMP), dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N,N-dimethylaminopropylamine, tetrahydrofuran (THF), toluene, acetone, diethyl ether, hexamethylphosphoramide, dimethylsulfoxide, benzene, xylene, quinoline, pyridine, methylnaphthalene, hexane, and the like. The above solvents may be used alone or in any combination.

[0062] Thickener A thickener is generally used to adjust the viscosity of the negative electrode slurry. The type of thickener is not particularly limited, and examples thereof include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above-mentioned thickeners may be used alone or in any combination.

[0063] In some embodiments, the content of the thickener is greater than about 0.1%, greater than about 0.5%, or greater than about 0.6% by weight of the negative electrode mixture layer. In some embodiments, the content of the thickener is less than about 5%, less than about 3%, or less than about 2% by weight of the negative electrode mixture layer. When the content of the thickener is within the above range, it is possible to suppress the decrease in capacity and the increase in resistance of the electrochemical device, and to ensure that the negative electrode slurry has good coating properties.

[0064] Surface Coating In some embodiments, a material different from the composition of the negative electrode mixture layer may be attached to the surface of the negative electrode mixture layer. Examples of the surface-attached material of the negative electrode mixture layer include, but are not limited to, oxides such as aluminum oxide, silica, titanium dioxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate.

[0065] Negative electrode active material content In some embodiments, the content of the negative electrode active material relative to the weight of the negative electrode mixture layer is greater than about 80%, greater than about 82%, or greater than about 84%. In some embodiments, the content of the negative electrode active material relative to the weight of the negative electrode mixture layer is less than about 99% or less than about 98%. In some embodiments, the content of the negative electrode active material relative to the weight of the negative electrode mixture layer is within the range consisting of any two of the above values.

[0066] Density of negative electrode active material In some embodiments, the density of the negative electrode active material in the negative electrode mixture layer is about 1 g / cm 3 Super, about 1.2g / cm 3 More than or about 1.3 g / cm 3 In some embodiments, the density of the negative electrode active material in the negative electrode mixture layer is greater than about 2.2 g / cm 3 Less than 2.1g / cm 3 Less than or about 2.0 g / cm 3 In some embodiments, the density of the negative electrode active material in the negative electrode mixture layer is within the range consisting of any two of the above values.

[0067] When the density of the negative electrode active material is within the above range, destruction of the negative electrode active material particles can be prevented, an increase in the initial irreversible capacity of the electrochemical device or deterioration of the charge / discharge characteristics at high current density due to a decrease in the permeability of the electrolyte in the vicinity of the negative electrode current collector / negative electrode active material interface can be suppressed, and further a decrease in the capacity and an increase in the resistance of the electrochemical device can be suppressed.

[0068] 2, negative electrode current collector Any known current collector may be used as the current collector that holds the negative electrode active material. Examples of the negative electrode current collector include, but are not limited to, metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper.

[0069] When the negative electrode current collector is a metal material, the form of the negative electrode current collector includes, but is not limited to, a metal foil, a metal cylinder, a metal strip coil, a metal plate, a metal film, an expanded metal, a punched metal, a metal foam, etc. In some embodiments, the negative electrode current collector is a metal film. In some embodiments, the negative electrode current collector is a copper foil. In some embodiments, the negative electrode current collector is a rolled copper foil by a rolling method or an electrolytic copper foil by an electrolytic method.

[0070] In some embodiments, the thickness of the negative electrode current collector is greater than about 1 μm or greater than about 5 μm. In some embodiments, the thickness of the negative electrode current collector is less than about 100 μm or less than about 50 μm. In some embodiments, the thickness of the negative electrode current collector is within the range consisting of any two of the above values.

[0071] The thickness ratio of the negative electrode mixture layer to the negative electrode current collector is a value obtained by dividing the thickness of the negative electrode mixture layer on one side by the thickness of the negative electrode current collector, and the value is not particularly limited. In some embodiments, the thickness ratio is 50 or less. In some embodiments, the thickness ratio is 30 or less. In some embodiments, the thickness ratio is 20 or less. In some embodiments, the thickness ratio is 10 or less. In some embodiments, the thickness ratio is 1 or more. In some embodiments, the thickness ratio is within a range consisting of any two of the above values. When the thickness ratio is within the above range, the capacity of the electrochemical device can be ensured and heat generation of the negative electrode current collector during charging and discharging at high current density can be suppressed.

[0072] II, electrolyte The electrolytic solution used in the electrochemical device of the present invention includes an electrolyte and a solvent that dissolves the electrolyte. In some embodiments, the electrolytic solution used in the electrochemical device of the present invention further includes an additive.

[0073] Another main feature of the electrochemical device of the present invention is that the electrolyte comprises a propionate ester.

[0074] In some embodiments, the propionate ester comprises a compound of Formula 2. [ka] R 1 is selected from ethyl or ethyl halide; R 2 is selected from a C1 to C6 alkyl group or a C1 to C6 halogenated alkyl group.

[0075] In some embodiments, the propionate ester includes, but is not limited to, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, pentyl propionate, halogenated methyl propionate, halogenated ethyl propionate, halogenated propyl propionate, halogenated butyl propionate, and halogenated pentyl propionate. In some embodiments, the propionate ester is selected from at least one of methyl propionate, ethyl propionate, propyl propionate, butyl propionate, and pentyl propionate. In some embodiments, the halogen group in the halogenated methyl propionate, halogenated ethyl propionate, halogenated propyl propionate, halogenated butyl propionate, and halogenated pentyl propionate is selected from one or more of a fluoro group (-F), a chloro group (-Cl), a bromo group (-Br), and an iodo group (-I). In some embodiments, the halogen group is a fluorine group (-F), which can provide better results.

[0076] In some embodiments, when the content of the propionate ester is X% based on the weight of the electrolyte, X is in the range of 5 to 65. In some embodiments, X is in the range of 10 to 60. In some embodiments, X is in the range of 15 to 50. In some embodiments, X is in the range of 20 to 40. In some embodiments, X is 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, or in a range consisting of any two of the above values. When the content of the propionate ester in the electrolyte is within the above range, the high temperature storage characteristics and overcharge resistance characteristics of the electrochemical device can be further improved.

[0077] In some examples, the propionate content in the electrolyte is X% and the adhesive strength is FN / cm. 2 satisfies 1.6≦F / X≦100. In some embodiments, 2≦F / X≦80. In some embodiments, 3≦F / X≦70. In some embodiments, 5≦F / X≦60. In some embodiments, 6≦F / X≦50. In some embodiments, F / X is 1.6, 3, 5, 7, 8, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100, or within a range consisting of any two of the preceding values. Content of propionate ester in electrolyte, X%, and adhesive strength, FN / cm 2 However, when the above relationship is satisfied, the high-temperature storage characteristics and overcharge resistance characteristics of the electrochemical device can be further improved. In some embodiments, the electrolyte further includes at least one of the following compounds: i) fluorocarbonates, ii) a compound having a cyano group, iii) lithium difluorophosphate, iv) a compound of formula 1, [ka] R 1 , R 2 , R 3 , R 4 , R 5 and R6 are each independently hydrogen or C1-C 10 is an alkyl group, L1 and L2 each independently represent -(CR 7 R 8 ) n-, R 7 and R 8 are each independently hydrogen or C1-C 10 is an alkyl group, and n is 1, 2 or 3.

[0078] i) Fluorocarbonates During charging and discharging of the electrochemical device, the fluorocarbonate acts together with the propionate ester to form a stable protective film on the surface of the negative electrode, thereby suppressing the decomposition reaction of the electrolyte.

[0079] In some embodiments, the fluorocarbonate has the formula C=O(OR x )(OR y ) and R x and R y are each selected from alkyl groups and halogenated alkyl groups having 1 to 6 carbon atoms; R x and R y At least one of R is selected from fluoroalkyl groups having 1 to 6 carbon atoms, and R x and R y optionally form a 5- to 7-membered ring together with the atom to which they are attached.

[0080] In some embodiments, examples of the fluorocarbonate include, but are not limited to, one or more of fluoroethylene carbonate, cis-4,4-difluoroethylene carbonate, trans-4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate, and ethyl trifluoroethyl carbonate.

[0081] In some embodiments, the amount of the fluorocarbonate is in the range of 0.1% to 10% by weight of the electrolyte. In some embodiments, the amount of the fluorocarbonate is in the range of 0.5% to 8% by weight of the electrolyte. In some embodiments, the amount of the fluorocarbonate is in the range of 1% to 5% by weight of the electrolyte. In some embodiments, the amount of the fluorocarbonate is 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any two of the ranges above.

[0082] ii) Compounds containing a cyano group In some embodiments, the compound having a cyano group is succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, ethylene glycol bis(propionitrile) ether, , 3,5-dioxaheptanedinitrile, 1,4-bis(cyanoethoxy)butane, diethylene glycol bis(2-cyanoethyl)ether, triethylene glycol bis(2-cyanoethyl)ether, tetraethylene glycol bis(2-cyanoethyl)ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol bis(4-cyanobutyl)ether, 1,4-dioxy Anhydrous butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3 -tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, and 1,2,5-tris(cyanoethoxy)pentane.

[0083] The above-mentioned compounds having a cyano group may be used alone or in combination. When the electrolyte solution contains two or more compounds having a cyano group, the content of the compound having a cyano group means the total content of the compounds having two or more cyano groups.

[0084] In some embodiments, when the content of the compound having a cyano group is b% based on the weight of the electrolyte, b is in the range of 0.01 to 10. In some embodiments, b is in the range of 0.05 to 8. In some embodiments, b is in the range of 0.1 to 5. In some embodiments, b is in the range of 0.5 to 3. In some embodiments, b is in the range of 1 to 2. In some embodiments, b is 0.01, 0.05, 0.1, 0.5, 1, 2, 5, 8, 10, or in a range consisting of any two of the above values. When the content of the compound having a cyano group in the electrolyte is in the above range, the high temperature storage characteristics and overcharge resistance characteristics of the electrochemical device can be further improved.

[0085] In some embodiments, the content X% of the propionic acid ester in the electrolyte and the content b% of the compound having a cyano group satisfy 0.5≦X / b≦200. In some embodiments, 1≦X / b≦150. In some embodiments, 5≦X / b≦100. In some embodiments, 10≦X / b≦80. In some embodiments, 30≦X / b≦50. In some embodiments, X / b is 0.5, 1, 5, 10, 20, 50, 80, 100, 120, 150, 180, 200, or within a range consisting of any two of the above values. When the content X% of the propionic acid ester in the electrolyte and the content b% of the compound having a cyano group satisfy the above relationship, the high temperature storage characteristics and overcharge resistance characteristics of the electrochemical device can be further improved.

[0086] iii) Lithium difluorophosphate (LiPO2F2) In some embodiments, the content of the lithium difluorophosphate is 0.01% to 1.5% by weight of the electrolyte. In some embodiments, the content of the lithium difluorophosphate is 0.05% to 1.2% by weight of the electrolyte. In some embodiments, the content of the lithium difluorophosphate is 0.1% to 1.0% by weight of the electrolyte. In some embodiments, the content of the lithium difluorophosphate is 0.5% to 0.8% by weight of the electrolyte. In some embodiments, the content of the lithium difluorophosphate is 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.8%, 1%, 1.5%, or within a range consisting of any two of the above values ​​by weight of the electrolyte.

[0087] iv) A compound of formula 1 In some embodiments, the compound of Formula 1 includes at least one of the following compounds: [ka]

[0088] In some embodiments, the content of the compound of formula 1 is in the range of 0.01% to 5% by weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is in the range of 0.05% to 4% by weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is in the range of 0.1% to 3% by weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is in the range of 0.5% to 2% by weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is in the range of 1% to 1.5% by weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or in a range consisting of any two of the above values ​​by weight of the electrolyte. When the content of the compound of formula 1 in the electrolyte is in the above range, the high temperature storage characteristic and the overcharge resistance characteristic of the electrochemical device can be further improved.

[0089] solvent In some embodiments, the electrolyte further comprises any non-aqueous solvent known in the art as a solvent for electrolytes.

[0090] In some embodiments, the non-aqueous solvent includes, but is not limited to, one or more of cyclic carbonates, linear carbonates, cyclic carboxylic acid esters, linear carboxylic acid esters, cyclic ethers, linear ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.

[0091] In some embodiments, examples of the cyclic carbonate include, but are not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate. In some embodiments, the cyclic carbonate has 3 to 6 carbon atoms.

[0092] In some embodiments, examples of the chain carbonate include, but are not limited to, one or more of chain carbonates such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl-n-propyl carbonate, ethyl-n-propyl carbonate, di-n-propyl carbonate, etc. Examples of fluorine-substituted chain carbonate include, but are not limited to, one or more of bis(fluoromethyl)carbonate, bis(difluoromethyl)carbonate, bis(trifluoromethyl)carbonate, bis(2-fluoroethyl)carbonate, bis(2,2-difluoroethyl)carbonate, bis(2,2,2-trifluoroethyl)carbonate, 2-fluoroethylmethylcarbonate, 2,2-difluoroethylmethylcarbonate, and 2,2,2-trifluoroethylmethylcarbonate.

[0093] In some embodiments, examples of the cyclic carboxylic acid ester include, but are not limited to, one or more of γ-butyrolactone and γ-valerolactone. In some embodiments, a portion of the hydrogen atoms in the cyclic carboxylic acid ester may be replaced with fluorine.

[0094] In some embodiments, examples of the chain carboxylic acid ester include, but are not limited to, one or more of methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate, ethyl pivalate, etc. In some embodiments, some of the hydrogen atoms in the chain carboxylic acid ester may be substituted with fluorine. In some embodiments, examples of the fluorine-substituted chain carboxylic acid ester include, but are not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate, and 2,2,2-trifluoroethyl trifluoroacetate.

[0095] In some embodiments, examples of the cyclic ether include, but are not limited to, one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, and dimethoxypropane.

[0096] In some embodiments, examples of the linear ether include, but are not limited to, one or more of dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane, and 1,2-ethoxymethoxyethane.

[0097] In some embodiments, examples of the phosphorus-containing organic solvent include, but are not limited to, one or more of trimethyl phosphate, triethyl phosphate, dimethylethyl phosphate, methyldiethyl phosphate, methylethylene phosphate, ethylethylene phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(2,2,3,3,3-pentafluoropropyl)phosphate, and the like.

[0098] In some embodiments, examples of the sulfur-containing organic solvent include, but are not limited to, one or more of sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethylsulfone, diethylsulfone, ethylmethylsulfone, methylpropylsulfone, dimethylsulfoxide, methylmethanesulfonate, ethylmethanesulfonate, methylethanesulfonate, ethylethanesulfonate, dimethylsulfate, diethylsulfate, and dibutylsulfate. In some embodiments, some of the hydrogen atoms in the sulfur-containing organic solvent may be replaced with fluorine.

[0099] In some embodiments, the aromatic fluorine-containing solvent includes, but is not limited to, one or more of fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.

[0100] In some embodiments, the solvent used in the electrolyte of the present invention includes a cyclic carbonate, a chain carbonate, a cyclic carboxylic acid ester, a chain carboxylic acid ester, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present invention includes an organic solvent selected from the group consisting of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, ethyl acetate, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present invention includes ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof.

[0101] Additives In some embodiments, examples of the additives include, but are not limited to, one or more of fluorocarbonates, vinyl esters of carbonic acid having a carbon-carbon double bond, compounds having a sulfur-oxygen double bond, and anhydrides.

[0102] In some embodiments, the content of the additive is 0.01% to 15%, 0.1% to 10%, or 1% to 5% by weight of the electrolyte.

[0103] According to an embodiment of the present invention, the content of the propionate ester is 1.5 to 30 times, 1.5 to 20 times, 2 to 20 times, or 5 to 20 times that of the additive, based on the weight of the electrolyte.

[0104] In some embodiments, the additive comprises one or more vinyl esters of carbon-carbon double bonds. Examples of vinyl esters of carbon-carbon double bonds include, but are not limited to, one or more of vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, fluoro vinylene carbonate, trifluoro methyl vinylene carbonate; vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1-ethyl-2-vinyl ethylene carbonate, 1-n-propyl-2-vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1,1-divinyl ethylene carbonate, 1,2-divinyl ethylene carbonate, 1,1-dimethyl-2-methylidene ethylene carbonate, and 1,1-diethyl-2-methylidene ethylene carbonate. In some embodiments, the vinyl carbonate containing a carbon-carbon double bond includes vinylene carbonate, which is easier to obtain and provides better results.

[0105] In some embodiments, the additive is a combination of a fluorocarbonate and a vinyl carbonate ester containing a carbon-carbon double bond. In some embodiments, the additive is a combination of a fluorocarbonate and a compound having a sulfur-oxygen double bond. In some embodiments, the additive is a combination of a fluorocarbonate and a compound having 2 to 4 cyano groups. In some embodiments, the additive is a combination of a fluorocarbonate and a cyclic carboxylic acid ester. In some embodiments, the additive is a combination of a fluorocarbonate and a cyclic phosphoric anhydride. In some embodiments, the additive is a combination of a fluorocarbonate and a carboxylic acid anhydride. In some embodiments, the additive is a combination of a fluorocarbonate and a sulfonic acid anhydride. In some embodiments, the additive is a combination of a fluorocarbonate and a carboxylic acid sulfonic acid anhydride.

[0106] Electrolytes The electrolyte is not particularly limited, and any known electrolyte can be used. In the case of a lithium secondary battery, a lithium salt is usually used.Examples of electrolytes include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, LiAlF4, LiSbF6, and LiWF7; lithium tungstates such as LiWOF5; lithium carboxylates such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, and CF3CF2CF2CF2CO2Li; FSO3Li, CH3SO3Li, CH2FSO3Li, CHF2SO3Li, CF3SO3Li, and CF3 Lithium sulfonates such as CF2SO3Li, CF3CF2CF2SO3Li, and CF3CF2CF2CF2SO3Li; lithium imide salts such as LiN(FCO)2, LiN(FCO)(FSO2), LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonylimide lithium, and cyclic 1,3-perfluoropropane bissulfonylimide lithium; LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5S Lithium methylated salts such as lithium methyl ester (Methyl ester) and lithium methyl ester (O2)3; lithium (malonate) borate salts such as lithium bis(malonate) borate and lithium difluoro(malonate) borate; lithium (malonate) phosphate salts such as lithium tris(malonate) phosphate, lithium difluorobis(malonate) phosphate, and lithium tetrafluoro(malonate) phosphate; and LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2F5 fluorine-containing organic lithium salts such as LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium oxalate borate salts such as lithium difluorooxalate borate, lithium bis(oxalate)borate; lithium oxalate phosphate salts such as lithium tetrafluorooxalate phosphate, lithium difluorobis(oxalate)phosphate, lithium tris(oxalate)phosphate, and the like.

[0107] In some embodiments, the electrolyte is selected from LiPF6, LiSbF6, FSO3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic lithium 1,2-perfluoroethanebissulfonylimide, cyclic lithium 1,3-perfluoropropanebissulfonylimide, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, lithium difluorooxalatoborate, lithium bis(oxalato)borate, and lithium difluorobis(oxalato)phosphate, which contribute to improving the output power characteristics, high rate charge / discharge characteristics, high temperature storage characteristics, and cycle characteristics of the electrochemical device.

[0108] The content of the electrolyte is not particularly limited as long as it does not impair the effect of the present invention. In some embodiments, the total molar concentration of lithium in the electrolyte is more than 0.3 mol / L, more than 0.4 mol / L, or more than 0.5 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L, or less than 2.0 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is within a range consisting of any two of the above values. When the electrolyte concentration is within the above range, the amount of lithium, which is a charged particle, is not too small, and the viscosity can be set to an appropriate range, making it easier to ensure good conductivity.

[0109] When two or more electrolytes are used, the electrolyte comprises at least one salt selected from the group consisting of monofluorophosphate, borate, oxalate, and fluorosulfonate. In some embodiments, the electrolyte comprises a salt selected from the group consisting of monofluorophosphate, oxalate, and fluorosulfonate. In some embodiments, the electrolyte comprises a lithium salt. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate, and fluorosulfonate is greater than 0.01% or greater than 0.1% by weight of the electrolyte. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate, and fluorosulfonate is less than 20% or less than 10% by weight of the electrolyte. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate, and fluorosulfonate is within the range consisting of any two of the above values.

[0110] In some embodiments, the electrolyte includes one or more selected from the group consisting of monofluorophosphates, borates, oxalates, and fluorosulfonates, and one or more other salts. The other salts can include the lithium salts exemplified above, and in some embodiments, LiPF6, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonylimide lithium, cyclic 1,3-perfluoropropane bissulfonylimide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3. In some embodiments, the other salt is LiPF6.

[0111] In some embodiments, the content of the other salts is greater than 0.01% or greater than 0.1% by weight of the electrolyte. In some embodiments, the content of the other salts is less than 20%, less than 15%, or less than 10% by weight of the electrolyte. In some embodiments, the content of the other salts is within a range consisting of any two of the above values. The other salts having the above content contribute to balancing the conductivity and viscosity of the electrolyte.

[0112] In addition to the above-mentioned solvent, additives, and electrolyte salt, the electrolyte may contain additional additives such as an anode film forming agent, a cathode protector, and an overcharge inhibitor, if necessary. As the additive, an additive generally used in a non-aqueous electrolyte secondary battery may be used, and examples thereof include, but are not limited to, vinylene carbonate, succinic anhydride, biphenyl, cyclohexylbenzene, 2,4-difluoroanisole, propane sultone, and propene sultone. These additives may be used alone or in combination. The content of these additives in the electrolyte is not particularly limited, and may be appropriately set depending on the type of the additive. In some embodiments, the content of the additive is less than 5%, in the range of 0.01% to 5%, or in the range of 0.2% to 5% by weight of the electrolyte.

[0113] III, positive electrode The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on one or two surfaces of the positive electrode current collector.

[0114] 1. Positive electrode active material layer The positive electrode active material layer includes a positive electrode active material. The positive electrode active material layer may be one layer or multiple layers. Each layer of the multiple layers of positive electrode active material may include the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly absorb and release metal ions such as lithium ions.

[0115] The type of the positive electrode active material is not particularly limited, and may be any material capable of electrochemically absorbing and releasing metal ions (e.g., lithium ions). In some embodiments, the positive electrode active material contains lithium and at least one transition metal. Examples of the positive electrode active material include, but are not limited to, lithium transition metal complex oxides and lithium-containing transition metal phosphate compounds.

[0116] In some embodiments, the transition metal in the lithium transition metal composite oxide includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium transition metal composite oxide includes lithium cobalt composite oxide such as LiCoO2, lithium nickel composite oxide such as LiNiO2, lithium manganese composite oxide such as LiMnO2, LiMn2O4, Li2MnO4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, in which some of the transition metal atoms that are the main components of these lithium transition metal complex oxides are replaced by other elements such as Na, K, B, F, Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, Nb, Mo, Sn, and W. An example of a lithium transition metal complex oxide is LiNi 0.5 Mn 0.5 O2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.45 Co 0.10 Al 0.45 O2, LiMn 1.8 Al 0.2 O4 and LiMn 1.5 Ni 0.5Examples of combinations of lithium transition metal composite oxides include, but are not limited to, combinations of LiCoO2 and LiMn2O4, and a part of Mn in LiMn2O4 may be replaced with a transition metal (e.g., LiNi 0.33 Co 0.33 Mn 0.33 O2), a part of the Co in LiCoO2 may be substituted with a transition metal.

[0117] In some embodiments, the transition metal in the lithium-containing transition metal phosphate compound includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium-containing transition metal phosphate compound includes iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, and cobalt phosphates such as LiCoPO4, and some of the transition metal atoms that are the main components of these lithium-containing transition metal phosphate compounds are replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, and Si.

[0118] In some embodiments, the positive electrode active material includes lithium phosphate, which can improve the continuous charging characteristics of the electrochemical device. The use of lithium phosphate is not limited. In some embodiments, the positive electrode active material and lithium phosphate are mixed and used. In some embodiments, the content of lithium phosphate is more than 0.1%, more than 0.3%, or more than 0.5% based on the weight of the positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is less than 10%, less than 8%, or less than 5% based on the weight of the positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is within the range consisting of any two of the above values.

[0119] Surface Coating A material different from the composition of the positive electrode active material may be attached to the surface of the positive electrode active material. Examples of the surface-attaching material include, but are not limited to, oxides such as aluminum oxide, silica, titanium dioxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; and carbon.

[0120] These surface-attaching substances can be attached to the surface of the positive electrode active material by a method of dissolving or suspending the surface-coating substance in a solvent, impregnating the positive electrode active material, and drying the same; a method of dissolving or suspending a surface-coating substance precursor in a solvent, impregnating the positive electrode active material, and then reacting the surface-coating substance by heating or the like; a method of adding the surface-coating substance precursor to the positive electrode active material and baking the surface-coating substance precursor, etc. When carbon is attached, a method of mechanically attaching a carbon material (e.g., activated carbon, etc.) may be used.

[0121] In some embodiments, the content of the surface-attaching material is greater than 0.1 ppm, greater than 1 ppm, or greater than 10 ppm, based on the weight of the positive electrode active material layer. In some embodiments, the content of the surface-coating material is less than 10%, less than 5%, or less than 2%, based on the weight of the positive electrode active material layer. In some embodiments, the content of the surface-coating material is within the range consisting of any two of the above values, based on the weight of the positive electrode active material layer.

[0122] By attaching a substance to the surface of the positive electrode active material, it is possible to suppress the oxidation reaction of the electrolyte on the surface of the positive electrode active material, and to improve the life of the electrochemical device. If the amount of the surface-attached substance is too small, the effect cannot be fully exerted, and if the amount of the surface-coating substance is too large, the ingress and egress of lithium ions is hindered, which may increase the resistance.

[0123] In the present invention, a positive electrode active material having a substance with a different composition attached to its surface is also referred to as a "positive electrode active material".

[0124] shape In some embodiments, the shapes of the positive electrode active material particles include, but are not limited to, chunks, polyhedrons, spheres, ellipsoids, plates, needles, and columns. In some embodiments, the positive electrode active material particles include primary particles, secondary particles, or combinations thereof. In some embodiments, the primary particles may aggregate to form secondary particles.

[0125] Tap Density In some embodiments, the tap density of the positive electrode active material is 0.5 g / cm 3 Super, 0.8g / cm 3 More than or equal to 1.0 g / cm 3 When the tap density of the positive electrode active material is within the above range, the amount of dispersion medium required for forming the positive electrode active material layer, as well as the amount of conductive material and positive electrode binder required, can be reduced, and this makes it possible to ensure the packing rate of the positive electrode active material and the capacity of the electrochemical device. By using a complex oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. Generally, the higher the tap density, the more preferable it is, and there is no particular upper limit. In some embodiments, the tap density of the positive electrode active material is 4.0 g / cm or less. 3 Less than 3.7g / cm 3 Less than or equal to 3.5g / cm 3 When the tap density of the positive electrode active material has the above upper limit, it is possible to suppress a decrease in the load characteristics.

[0126] The tap density of the positive electrode active material can be calculated by the following method: 5 g to 10 g of the positive electrode active material powder is placed in a 10 mL glass measuring cylinder, and vibration is performed 200 times with a stroke of 20 mm to obtain the powder packing density (tap density).

[0127] Median diameter (D50) When the positive electrode active material particles are primary particles, the median diameter (D50) of the positive electrode active material particles means the primary particle diameter of the positive electrode active material particles. When the primary particles of the positive electrode active material particles are aggregated to form secondary particles, the median diameter (D50) of the positive electrode active material particles means the secondary particle diameter of the positive electrode active material particles.

[0128] In some embodiments, the median diameter (D50) of the positive electrode active material particles is greater than 0.3 μm, greater than 0.5 μm, greater than 0.8 μm, or greater than 1.0 μm. In some embodiments, the median diameter (D50) of the positive electrode active material particles is less than 30 μm, less than 27 μm, less than 25 μm, or less than 22 μm. In some embodiments, the median diameter (D50) of the positive electrode active material particles is within a range consisting of any two of the above values. When the median diameter (D50) of the positive electrode active material particles is within the above range, a positive electrode active material with a high tap density can be obtained, and deterioration of the characteristics of the electrochemical device can be suppressed. Meanwhile, problems such as streaking can be prevented in the process of preparing the positive electrode of the electrochemical device (i.e., when the positive electrode active material, conductive material, binder, etc. are slurried with a solvent and applied in the form of a film). Here, by mixing two or more types of positive electrode active materials with different median diameters, the filling property during the preparation of the positive electrode can be further improved.

[0129] The median diameter (D50) of the positive electrode active material particles can be measured by a laser diffraction / scattering type particle size distribution analyzer. When using HORIBA's LA-920 as the particle size distribution analyzer, a 0.1% sodium hexametaphosphate aqueous solution is used as the dispersion medium used during measurement, and after dispersing with ultrasonic waves for 5 minutes, the measurement refractive index is set to 1.24 and measurement is performed.

[0130] Average primary particle size When the primary particles of the positive electrode active material particles are aggregated to form secondary particles, in some embodiments, the average primary particle size of the positive electrode active material is greater than 0.05 μm, greater than 0.1 μm, or greater than 0.5 μm. In some embodiments, the average primary particle size of the positive electrode active material is less than 5 μm, less than 4 μm, less than 3 μm, or less than 2 μm. In some embodiments, the average primary particle size of the positive electrode active material is within a range consisting of any two of the above values. When the average primary particle size of the positive electrode active material is within the above range, powder packing and specific surface area can be ensured, deterioration of battery characteristics can be suppressed, and appropriate crystallinity can be obtained, thereby ensuring the reversibility of charging and discharging of the electrochemical device.

[0131] The average primary particle diameter of the positive electrode active material can be obtained by observing an image obtained by a scanning electron microscope (SEM). In an SEM image at a magnification of 10,000 times, the longest intercepts obtained from the left and right boundaries of the primary particles with respect to a horizontal line are calculated for any 50 primary particles, and the average of these is calculated to obtain the average primary particle diameter.

[0132] Specific surface area (BET) In some embodiments, the specific surface area (BET) of the positive electrode active material is less than 0.1 m 2 / g, 0.2m 2 / g or more than 0.3m 2 In some embodiments, the specific surface area (BET) of the positive electrode active material is greater than 50 m 2 / g, less than 40m 2 / g or less than 30m 2 / g. In some embodiments, the specific surface area (BET) of the positive electrode active material is within the range consisting of any two of the above values. When the specific surface area (BET) of the positive electrode active material is within the above range, the characteristics of the electrochemical device can be ensured and the positive electrode active material can have good coating properties.

[0133] The specific surface area (BET) of the positive electrode active material can be measured by the following method: Using a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken), the sample is pre-dried at 150°C for 30 minutes under a nitrogen stream, and then the measurement is performed by the nitrogen adsorption single-point BET method using a nitrogen-helium mixed gas in which the relative pressure of the nitrogen gas to the atmospheric pressure is precisely adjusted to 0.3.

[0134] Positive Electrode Conductive Material The type of the positive electrode conductive material is not particularly limited, and any known conductive material may be used. Examples of the positive electrode conductive material include, but are not limited to, graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; carbon materials such as amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in combination.

[0135] In some embodiments, the content of the positive electrode conductive material is greater than 0.01%, greater than 0.1%, or greater than 1% by weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode conductive material is less than 10%, less than 8%, or less than 5% by weight of the positive electrode active material layer. When the content of the positive electrode conductive material is within the above range, sufficient conductivity and capacity of the electrochemical device can be ensured.

[0136] Positive electrode binder The type of positive electrode binder used in producing the positive electrode active material layer is not particularly limited, and in the case of a coating method, any material may be used as long as it can be dissolved or dispersed in the liquid medium used in producing the electrode. Examples of the positive electrode binder include, but are not limited to, one or more of: resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber-like polymers such as styrene butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, butadiene rubber, and ethylene-propylene rubber; thermoplastic elastomeric polymers such as ethylene-propylene-diene terpolymer (EPDM), styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, or hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, and propylene-α-olefin copolymer; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluoropolyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer; and polymer compositions having ionic conductivity for alkali metal ions (particularly, lithium ions). The positive electrode binders may be used alone or in any combination.

[0137] In some embodiments, the content of the positive electrode binder is greater than 0.1%, greater than 1%, or greater than 1.5% by weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode binder is less than 10%, less than 5%, or less than 3% by weight of the positive electrode active material layer. When the content of the positive electrode binder is within the above range, the positive electrode has good electrical conductivity and sufficient mechanical strength, and the capacity of the electrochemical device can be ensured.

[0138] solvent The type of solvent for forming the positive electrode slurry is not limited, and may be any solvent capable of dissolving or dispersing the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as necessary. Examples of the solvent for forming the positive electrode slurry may include any one of an aqueous solvent and an organic solvent. Examples of the aqueous medium include, but are not limited to, water, and a mixed medium of alcohol and water. Examples of organic media include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; and aprotic polar solvents such as hexamethylphosphoramide and dimethylsulfoxide.

[0139] Thickener A thickener is generally used to adjust the viscosity of a slurry. When an aqueous medium is used, a thickener and a styrene butadiene rubber (SBR) emulsion may be used to form a slurry. The type of thickener is not particularly limited, and examples thereof include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above-mentioned thickeners may be used alone or in any combination.

[0140] In some embodiments, the content of the thickener is greater than 0.1%, greater than 0.2%, or greater than 0.3% by weight of the positive electrode active material layer. In some embodiments, the content of the thickener is less than 5%, less than 3%, or less than 2% by weight of the positive electrode active material layer. In some embodiments, the content of the thickener is within a range consisting of any two of the above values ​​by weight of the positive electrode active material layer. When the content of the thickener is within the above range, the positive electrode slurry can have good coating properties, and the decrease in capacity and the increase in resistance of the electrochemical device can be suppressed.

[0141] Positive electrode active material content In some embodiments, the content of the positive electrode active material is greater than 80%, greater than 82%, or greater than 84% by weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode active material is less than 99% or less than 98% by weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode active material is within a range consisting of any two of the above values ​​by weight of the positive electrode active material layer. When the content of the positive electrode active material is within the above range, the electric capacity of the positive electrode active material in the positive electrode active material layer can be ensured and the strength of the positive electrode can be maintained.

[0142] Density of the positive electrode active material layer The positive electrode active material layer obtained by coating and drying may be subjected to a pressing process using a hand press, a roll press, or the like in order to increase the packing density of the positive electrode active material. In some embodiments, the density of the positive electrode active material layer is 1.5 g / cm 3 Super, 2g / cm 3 More than 2.2 g / cm 3 In some embodiments, the density of the positive electrode active material layer is greater than 5 g / cm 3 Less than 4.5g / cm 3 Less than or equal to 4g / cm 3 In some embodiments, the density of the positive electrode active material layer is within a range consisting of any two of the above values. When the density of the positive electrode active material layer is within the above range, the electrochemical device can have good charge / discharge characteristics and can suppress an increase in resistance.

[0143] Thickness of the positive electrode active material layer By thickness of the positive electrode active material layer is meant the thickness of the positive electrode active material layer on either side of the positive electrode current collector. In some embodiments, the thickness of the positive electrode active material layer is greater than 10 μm or greater than 20 μm. In some embodiments, the thickness of the positive electrode active material layer is less than 500 μm or less than 450 μm.

[0144] Manufacturing method of positive electrode active material The positive electrode active material can be produced by a normal method for producing inorganic compounds. In order to produce a spherical or ellipsoidal positive electrode active material, the following production method can be adopted. The raw material of the transition metal is dissolved or crushed and dispersed in a solvent such as water, and the pH is adjusted while stirring to produce and recover a spherical precursor. If necessary, it is dried, and then a Li source such as LiOH, Li2CO3, or LiNO3 is added and calcined at a high temperature to obtain a positive electrode active material.

[0145] 2, Positive electrode current collector The type of the positive electrode current collector is not particularly limited, and may be any known material suitable as a positive electrode current collector. Examples of the positive electrode current collector include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, etc.; carbon materials such as carbon cloth, carbon paper, etc. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0146] The form of the positive electrode current collector is not particularly limited. When the positive electrode current collector is a metal material, the form of the positive electrode current collector includes, but is not limited to, a metal foil, a metal cylinder, a metal strip coil, a metal plate, a metal film, an expanded metal, a punched metal, a foam metal, and the like. When the positive electrode current collector is a carbon material, the form of the positive electrode current collector includes, but is not limited to, a carbon plate, a carbon film, a carbon cylinder, and the like. In some embodiments, the positive electrode current collector is a metal foil. In some embodiments, the metal foil is in a mesh form. The thickness of the metal foil is not particularly limited. In some embodiments, the thickness of the metal foil is greater than 1 μm, greater than 3 μm, or greater than 5 μm. In some embodiments, the thickness of the metal foil is less than 1 μm, less than 100 μm, or less than about 50 μm. In some embodiments, the thickness of the metal foil is within the range consisting of any two of the above values.

[0147] In order to reduce the electrical contact resistance between the positive electrode current collector and the positive electrode active material layer, the surface of the positive electrode current collector may include a conductive additive. Examples of the conductive additive include, but are not limited to, carbon and precious metals such as gold, platinum, and silver.

[0148] The thickness ratio of the positive electrode active material layer to the positive electrode current collector is the value obtained by dividing the thickness of the positive electrode active material layer on one side by the thickness of the positive electrode current collector, and the value is not particularly limited. In some embodiments, the thickness ratio is less than 50, less than 30, or less than 20. In some embodiments, the thickness ratio is greater than 0.5, greater than 0.8, or greater than 1. In some embodiments, the thickness ratio is within a range consisting of any two of the above values. When the thickness ratio is within the above range, heat generation from the positive electrode current collector during charging and discharging at high current density can be suppressed, and the capacity of the electrochemical device can be ensured.

[0149] 3. How to make the positive electrode The positive electrode can be produced by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector. The positive electrode using the positive electrode active material can be produced by a conventional method. That is, the positive electrode active material and the binder, as well as a conductive material and a thickener as necessary, are dry-mixed, formed into a sheet, and the obtained sheet is pressed against a positive electrode current collector, or these materials are dissolved or dispersed in a liquid medium to prepare a slurry, which is applied to a positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode.

[0150] IV, separator In order to prevent short circuits, a separator is usually placed between the positive electrode and the negative electrode, and in this case, the electrolyte of the present invention is usually used by impregnating the separator.

[0151] The material and shape of the separator are not particularly limited, and may be any material that does not significantly impair the effects of the present invention. The separator may be a resin, glass fiber, inorganic material, etc., formed of a material stable to the electrolyte of the present invention. In some embodiments, the separator includes a porous sheet or nonwoven fabric having excellent liquid retention. Examples of materials for the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The above separator materials may be used alone or in any combination.

[0152] The separator may be a material formed by laminating the above-mentioned materials, and examples thereof include, but are not limited to, a three-layer separator in which polypropylene, polyethylene, and polypropylene are laminated in this order.

[0153] Examples of inorganic materials include, but are not limited to, oxides such as aluminum oxide and silica, nitrides such as aluminum nitride and silicon nitride, sulfates (e.g., barium sulfate, calcium sulfate, etc.) The forms of the inorganic materials include, but are not limited to, particulate or fibrous.

[0154] The separator may be in the form of a film, examples of which include, but are not limited to, nonwoven fabric, woven fabric, microporous membrane, etc. When the separator is in the form of a film, the pore size is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In addition to the above independent film-like separator, a separator formed by forming a composite porous layer containing the above inorganic particles on the surface of the positive electrode and / or negative electrode using a resin-based binder, for example, a separator formed by forming a porous layer on both sides of the positive electrode with aluminum oxide particles having a 90% particle size of less than 1 μm using a fluororesin as a binder, may be used.

[0155] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is more than 1 μm, more than 5 μm, or more than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the separator is within a range consisting of any two of the above values. When the thickness of the separator is within the above range, insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.

[0156] When a porous material such as a porous sheet or nonwoven fabric is used as the separator, the porosity of the separator is arbitrary. In some embodiments, the porosity of the separator is more than 10%, more than 15%, or more than 20%. In some embodiments, the porosity of the separator is less than 60%, less than 50%, or less than 45%. In some embodiments, the porosity of the separator is within a range consisting of any two of the above values. When the porosity of the separator is within the above range, the insulation property and mechanical strength can be ensured, the sheet resistance can be suppressed, and the electrochemical device can have good safety characteristics.

[0157] The average pore size of the separator is also arbitrary. In some embodiments, the average pore size of the separator is less than 0.5 μm or less than 0.2 μm. In some embodiments, the average pore size of the separator is greater than 0.05 μm. In some embodiments, the average pore size of the separator is within a range consisting of any two of the above values. If the average pore size of the separator exceeds the above range, a short circuit is likely to occur. If the average pore size of the separator is within the above range, the electrochemical device can have good safety characteristics.

[0158] V. Electrochemical device assembly The electrochemical device assembly includes an electrode group, a current collecting structure, an exterior case, and a protective element.

[0159] electrode group The electrode group may have either a laminated structure in which the positive electrode and the negative electrode are laminated with the separator interposed therebetween, or a structure in which the positive electrode and the negative electrode are spirally wound with the separator interposed therebetween. In some embodiments, the mass ratio of the electrode group to the internal volume of the battery (electrode group occupancy rate) is more than 40% or more than 50%. In some embodiments, the electrode group occupancy rate is less than 90% or less than 80%. In some embodiments, the electrode group occupancy rate is within a range consisting of any two of the above values. When the electrode group occupancy rate is within the above range, the capacity of the electrochemical device can be ensured, and deterioration of characteristics such as repeated charge / discharge characteristics and high-temperature storage characteristics due to an increase in internal pressure can be suppressed.

[0160] Current collection structure The current collecting structure is not particularly limited. In some embodiments, the current collecting structure is a structure for reducing the resistance of the wiring portion and the joint portion. When the electrode group has the above-mentioned laminated structure, a structure in which the metal core portions of the electrode layers are bundled and welded to a terminal is preferably used. Since the internal resistance increases when the area of ​​one electrode increases, it is also preferable to provide two or more terminals in the electrode to reduce the resistance. When the electrode group has the above-mentioned wound structure, the internal resistance can be reduced by providing two or more lead structures on each of the positive electrode and the negative electrode and bundling them on the terminal.

[0161] Outer case The material of the outer case is not particularly limited, and may be any material that is stable against the electrolyte used. The outer case may be made of metals such as nickel-plated steel, stainless steel, aluminum, aluminum alloy, magnesium alloy, or a laminated film of resin and aluminum foil, but is not limited thereto. In some embodiments, the outer case is a metal or laminated film of aluminum or aluminum alloy.

[0162] The metal exterior case includes, but is not limited to, a sealed structure formed by welding metals together by laser welding, resistance welding, or ultrasonic welding; or a caulking structure formed by using the above metals via a resin gasket. The exterior case using the laminated film includes, but is not limited to, a sealed structure formed by heat fusing resin layers together. In order to improve the sealing property, a resin different from the resin used in the laminated film may be interposed between the resin layers. When the resin layer is heat-sealed by the current collecting terminal to form a sealed structure, a resin having a polar group or a modified resin into which a polar group has been introduced may be used as the interposed resin by bonding the metal and the resin. The shape of the exterior case is also arbitrary, and may be, for example, any of a cylindrical shape, a square shape, a laminated type, a button type, a large size, etc.

[0163] Protection Device The protective element may be a thermal fuse having a positive temperature coefficient (PTC) whose resistance increases when abnormal heat is generated or an excessive current flows, a thermistor, a valve (current cutoff valve) that cuts off the current flowing in the circuit by suddenly increasing the internal pressure or temperature of the battery when abnormal heat is generated, etc. The protective element may be selected so that it does not operate under normal use conditions at high current, or may be designed so that abnormal heat generation or thermal runaway does not occur even if the protective element is not present.

[0164] VI. Application The electrochemical device of the present invention includes any device in which an electrochemical reaction occurs, and specific examples thereof include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery or a lithium ion secondary battery.

[0165] The present invention further provides an electronic device comprising an electrochemical device according to the present invention.

[0166] The use of the electrochemical device of the present invention is not particularly limited and may be used in any electronic device known in the prior art. In some embodiments, the electrochemical device of the present invention includes, but is not limited to, laptops, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copiers, portable printers, stereo headsets, video recorders, LCD televisions, portable cleaners, portable CD players, minidiscs, walkie-talkies, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, bicycle auxiliaries, bicycles, lighting equipment, toys, game consoles, watches, power tools, flashlights, cameras, large household batteries, and lithium ion capacitors.

[0167] Hereinafter, the preparation of a lithium ion battery is described with reference to specific examples by taking a lithium ion battery as an example, and those skilled in the art should understand that the preparation methods described in the present invention are merely exemplary, and any other suitable preparation methods are within the scope of the present invention. Working Example

[0168] In the following, examples and comparative examples of the lithium ion battery according to the present invention will be described and the characteristics will be evaluated.

[0169] 1. Preparation of lithium-ion batteries 1. Preparation of the negative electrode Artificial graphite, rubber, and sodium carboxymethylcellulose were mixed with deionized water in a mass ratio of 96%:2%:2% and stirred uniformly to obtain a negative electrode slurry. This negative electrode slurry was applied to a 12 μm current collector. It was dried and cold rolled, then cut and tab-welded to obtain a negative electrode.

[0170] [Table 1-1]

[0171] 2. Preparation of the positive electrode Lithium cobalt oxide (LiCoO2), conductive material (Super-P), and polyvinylidene fluoride (PVDF) were mixed with N-methylpyrrolidone (NMP) in a mass ratio of 95%:2%:3% and stirred uniformly to obtain a positive electrode slurry. This positive electrode slurry was applied to a 12μm aluminum foil, dried, cold rolled, and then cut and tabs were welded to obtain a positive electrode.

[0172] 3. Preparation of electrolyte In a dry argon gas atmosphere, EC, PC and DEC (weight ratio 1:1:1) were mixed, and LiPF6 was added and mixed uniformly to form a base electrolyte, the concentration of LiPF6 was 1.15 mol / L. Different amounts of additives were added to the base electrolyte to obtain electrolytes of different examples and comparative examples. The abbreviations and names of the components in the electrolyte are shown in the table below.

[0173] [Table 1-2]

[0174] 4. Preparation of Separator A polyethylene (PE) porous polymer film was used as the separator.

[0175] 5. Preparation of Lithium-ion Battery The obtained positive electrode, separator, and negative electrode were wound in this order and housed in an exterior foil, leaving an inlet through which an electrolyte was poured, packaged, and then subjected to processes such as formation and capacity measurement to obtain a lithium ion battery.

[0176] 2.Measurement method 1. Measurement method for high-temperature storage expansion rate of lithium-ion batteries The lithium-ion battery was left at 25°C for 30 minutes, then charged at a constant current of 0.5C to 4.45V, and then charged at a constant voltage of 0.05C at 4.45V, and left at rest for 5 minutes, after which the thickness of the lithium-ion battery was measured. After storing at 60°C for 21 days, the thickness of the lithium-ion battery was measured again. The high-temperature storage expansion rate of the lithium-ion battery was calculated using the following formula:

[0177] High temperature storage expansion rate = [(thickness after storage - thickness before storage) / thickness before storage] x 100%.

[0178] 2. Measurement method for the overcharge deformation rate of lithium-ion batteries The lithium-ion battery was left to stand at 25°C for 30 minutes, then charged at a constant current of 0.5C to 4.45V, then charged at a constant voltage of 0.05C at 4.45V, left to stand for 60 minutes, and the thickness T1 of the lithium-ion battery was measured. Next, the battery was charged at a constant current of 0.1C for 60 minutes and left to stand for 30 minutes. This step was repeated five times to bring the lithium-ion battery to a 150% state of charge (SOC), and the thickness T2 of the lithium-ion battery was measured.

[0179] Overcharge deformation rate = [(T2-T1) / T1] × 100%.

[0180] 3. Measurement results Table 1 shows the influence of the adhesive strength between the negative electrode active materials and the propionic acid ester in the electrolyte on the high temperature storage expansion rate and overcharge deformation rate of the lithium ion battery.

[0181] [Table 1]

[0182] As can be seen from the results, the adhesive strength between the negative electrode active materials is 100N / cm 2 ~500N / cm 2 In addition, when the electrolyte contains a propionic acid ester, it can suppress the expansion / contraction of the negative electrode during the charge / discharge process and stabilize the interface between the negative electrode mixture layer and the electrolyte, thereby significantly reducing the high-temperature storage expansion rate and overcharge deformation rate of the lithium ion battery.

[0183] Adhesive strength between negative electrode active materials FN / cm 2 and the content X% of the propionate ester in the electrolyte satisfy 1.6≦F / X≦100, the high-temperature storage expansion rate and overcharge deformation rate of the lithium ion battery can be further reduced.

[0184] Table 2 shows the influence of the specific surface area of ​​the negative electrode mixture layer on the high-temperature storage expansion rate and overcharge deformation rate in the lithium ion battery characteristics. Examples 2-1 to 2-6 are distinguished from Example 1-1 or Example 1-5 only by the parameters shown in Table 2.

[0185] [Table 2]

[0186] As can be seen from the results, the specific surface area of ​​the negative electrode mixture layer is 2m 2 / g~5m 2 / g, the high-temperature storage expansion rate and overcharge deformation rate of the lithium ion battery can be further reduced. 2 / g and adhesive strength between negative electrode active material FN / cm 2 When the relationship 20≦F / A≦250 is satisfied, the high-temperature storage expansion rate and overcharge deformation rate of the lithium ion battery can be further reduced.

[0187] Table 3 shows the influence of trace metals in the negative electrode active material on the high-temperature storage expansion rate and overcharge deformation rate of a lithium ion battery. The only difference between Examples 3-1 to 3-8 and Example 1-1 is the parameters shown in Table 3.

[0188] [Table 3]

[0189] As can be seen from the results, when the negative electrode active material contains trace metal elements (iron, molybdenum and / or copper), the high temperature storage expansion rate and overcharge deformation rate of the lithium ion battery can be further reduced.

[0190] Table 4 shows the influence of the composition of the electrolyte on the high-temperature storage expansion rate and overcharge deformation rate of the lithium ion battery. The only difference between Examples 4-1 to 4-31 and Example 1-1 is the parameters shown in Table 4.

[0191] [Table 4]

[0192] As can be seen from the results, the adhesive strength between the negative electrode active materials is 100N / cm 2 ~500N / cm 2 and the electrolyte contains a propionate ester and further contains a fluorocarbonate, an organic compound having a cyano group, lithium difluorophosphate, and / or a compound of formula 1, the high-temperature storage expansion rate and overcharge deformation rate of the lithium ion battery can be further reduced.

[0193] Table 5 shows the effect of the relationship between the content of propionate ester in the electrolyte (X%) and the organic compound having a cyano group (b%) on the high-temperature storage expansion rate and overcharge deformation rate of the lithium-ion battery. The only difference between Examples 5-1 to 5-8 and Example 1-1 or Example 4-3 is the parameters shown in Table 5.

[0194] [Table 5]

[0195] As can be seen from the results, when the content of the organic compound having a cyano group in the electrolyte is 0.01% to 10%, the high-temperature storage expansion rate and overcharge deformation rate of the lithium-ion battery can be further reduced. When the content of the propionate ester in the electrolyte, X%, and the content of the organic compound having a cyano group, b%, satisfy 0.5≦X / b≦200, the high-temperature storage expansion rate and overcharge deformation rate of the lithium-ion battery can be further reduced.

[0196] Throughout the specification, references to "an embodiment," "some embodiments," "one embodiment," "another example," "an example," "embodiment," or "some examples" mean that at least one embodiment or example of the invention includes a particular feature, structure, material, or characteristic described in that embodiment or example. Thus, the appearances of, for example, "in some embodiments," "in an embodiment," "in one embodiment," "in another example," "in one example," "in a particular example," or "an example" in various places throughout the specification do not necessarily refer to the same embodiment or example of the invention. Furthermore, particular features, structures, materials, or characteristics herein may be combined in any suitable manner in one or more embodiments or examples.

[0197] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above-described embodiments should not be construed as limiting the present invention, and that modifications, substitutions, and alterations can be made to the embodiments without departing from the spirit, principle, and scope of the present invention.

Claims

1. An electrochemical device comprising a positive electrode, a negative electrode, and an electrolyte, the negative electrode includes a negative electrode current collector and a negative electrode mixture layer formed on the negative electrode current collector, The negative electrode mixture layer contains a negative electrode active material, When the adhesive strength between the negative electrode active materials is F N / cm2, F is in the range of 100 to 500, the electrolyte solution comprises a propionate ester; When the specific surface area of ​​the negative electrode mixture layer is A m2 / g, A is in the range of 2 to 5, An electrochemical device, where F and A satisfy 20≦F / A≦250.

2. The negative electrode mixture layer contains rubber, 10. The electrochemical device of claim 1, wherein the rubber comprises at least one of styrene-butadiene rubber, isoprene rubber, butadiene rubber, fluororubber, acrylonitrile-butadiene rubber, and styrene-propylene rubber.

3. 3. The electrochemical device of claim 2, wherein the rubber further comprises at least one of acrylic, chlorotrifluoroethylene, and hexafluoropropylene functional groups.

4. 2. The electrochemical device according to claim 1, wherein when the content of the propionic acid ester is X% with respect to the weight of the electrolyte, X is in the range of 5 to 65.

5. The electrochemical device according to claim 4 , wherein F and X satisfy 1.6≦F / X≦100.

6. The negative electrode active material is (a) having a median diameter of 5 μm to 30 μm; (b) comprising at least one of artificial graphite, natural graphite, mesocarbon microbeads, soft carbon, hard carbon, amorphous carbon, a silicon-containing material, a tin-containing material, and an alloy material; (c) containing a metal, the metal containing at least one of molybdenum, iron, and copper, and the content of the metal relative to the weight of the negative electrode mixture layer is 0.05% or less; The electrochemical device according to claim 1 , wherein at least one of the following is satisfied:

7. The electrolyte solution is a) a fluorocarbonate; b) a compound having a cyano group; and c) lithium difluorophosphate; and d) a compound of formula 1; and and further comprising at least one of 【Chemistry 6】 R1, R2, R3, R4, R5, and R6 are each independently hydrogen or a C1-C10 alkyl group; L1 and L2 are each independently -(CR7R8)n-; R7 and R8 are each independently hydrogen or a C1-C10 alkyl group; and 2. The electrochemical device of claim 1 , wherein n is 1, 2, or 3.

8. The compound of formula 1 is 【Chemistry 7】 8. The electrochemical device of claim 7, comprising at least one of:

9. 8. The electrochemical device according to claim 7, wherein the content of the compound of formula 1 is in the range of 0.01% to 5% by weight of the electrolyte.

10. 8. The electrochemical device according to claim 7, wherein b is in the range of 0.01 to 10, where b % is the content of the compound having a cyano group relative to the weight of the electrolyte.

11. 11. The electrochemical device according to claim 10, wherein, when the content of the propionic acid ester is X% relative to the weight of the electrolyte, X is in the range of 5 to 65, and X and b satisfy 0.5≦X / b≦200.

12. An electronic device comprising an electrochemical device according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Electrode active material, electrode and energy storage device including the same, and method of preparing the electrode active material

    CN106169574A

  • Nonaqueous electrolyte secondary battery

    JP2007242374A

  • Nonaqueous electrolyte composition and nonaqueous electrolyte battery

    JP2009123497A

  • Electrode for lithium secondary battery, and lithium secondary battery

    JP2011204578A

  • Nonaqueous electrolyte for lithium secondary battery and lithium secondary battery containing the same

    JP2020528640A